Development of flood exposure and loss scenarios for S.E. Asia - Lim, Christopher Yeh Han (Nanyang Technological University, 2023)
In the past two decades, floods have accounted for nearly half of all natural disasters and severely impacted livelihoods, properties and economies. With climate change intensifying the occurrence and impacts of floods, it is now even more essential for flood prone countries to be equipped with appropriate mitigative measures. This project utilizes Quantum Geographic Information System (QGIS) to study the flood exposure and economic loss scenarios in Hanoi, a densely populated coastal province in Vietnam that is encompassed by low-lying river deltas. Critically affected districts in Hanoi were identified by analyzing the population and sector asset values affected. Through a cost-benefit analysis of flood control structures applied to a district in Hanoi, this research aims to underline the consequences of floods and establish the importance of flood mitigation.